Diabetes and stroke in Qatar: results of a prospective stroke register. Issue 2 (August 2015) - Butler, Jo; Bourke, Paula Jayne
Abstract : Background: Stroke prevalence is on the increase within Qatar, both within the local indigenous population and the migrants coming into the country for work. There is a perception that diabetes is a major contributing factor in many of the stroke patients but there is a lack of evidence. People with diabetes have a higher risk of stroke disease and within Qatar there has been a rise in people having stroke of 26% per 100, 000 head of population in the last decade Aim: A population-based study, which describes the epidemiology of stroke in respect to presenting HbA1c level. Methods: The HbA1c level was recorded in 919 patients admitted to hospital during 2014 with a primary diagnosis of ischaemic or haemorrhagic stroke. The patients were divided into three groups according to their HbA1c levels: HbA1c≥ 6.5% (a diagnosis of diabetes), HbA1c 5.7–6.4% (pre-diabetes) and HbA1c≤ 5.6% (normal range). Each group was compared by subtype of stroke, ethnic group, age and gender. Results. The results indicate that Qataris and Arabs are more at risk than other ethnic groups of lacunar infarcts. The average age varies from 49 years for the West Pacific population to 67 years for Qataris. In Qatari nationals, the gender is almost equally divided. Conclusion: The prevalence of HbA1c≥ 5.7% in the stroke population is on average 77%, whereas in the Qatari stroke population this rises to 88%. The group of patients with HbA1c≥ 6.5% features more prominently in all subtypes of ischaemic strokes.